2003
DOI: 10.1021/ma020840t
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Capsules Prepared by in Situ Synthesis and Cross-Linking of Amphiphilic Copolymer by Atom Transfer Radical Polymerization

Abstract: A technique for encapsulation of polar organic solvents using atom transfer radical polymerization (ATRP) by suspension polymerization was developed to encapsulate diphenyl ether (solubility parameter δ = 20.9 MPa1/2) for the first time. An amphiphilic terpolymer was prepared by suspension polymerization, by first preparing poly(methyl methacrylate-co-poly(ethylene glycol) methacrylate), P(MMA-co-PegMA), oligomers in solution conditions, followed by addition of a cross-linking monomer, diethylene glycol dimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 22 publications
1
44
0
Order By: Relevance
“…They found that a combination of two processes, liquid–liquid emulsion and solid–liquid dispersion polymerization, was operative. More recently, the copper‐mediated ATRP of MMA in an aqueous suspension of diphenyl ether was used to prepare crosslinked hollow polymer particles about 50–100 μm in diameter 14. Zhu et al15 reported ATRP of MMA in an aqueous suspension and found a typical ATRP behavior under direct suspension conditions, although they used a water‐soluble catalyst system (CuCl/bipyridine).…”
Section: Methodsmentioning
confidence: 99%
“…They found that a combination of two processes, liquid–liquid emulsion and solid–liquid dispersion polymerization, was operative. More recently, the copper‐mediated ATRP of MMA in an aqueous suspension of diphenyl ether was used to prepare crosslinked hollow polymer particles about 50–100 μm in diameter 14. Zhu et al15 reported ATRP of MMA in an aqueous suspension and found a typical ATRP behavior under direct suspension conditions, although they used a water‐soluble catalyst system (CuCl/bipyridine).…”
Section: Methodsmentioning
confidence: 99%
“…[59] To the best of our knowledge, the present work constitutes the first example of formation of hollow particles in a dispersed NMP process (Figure 8c). Hollow particle synthesis has previously been reported using ATRP [60,61] and RAFT. [62][63][64][65][66] The present results demonstrate that the SaPSeP method is applicable also to NMP systems, thus providing a convenient synthetic route to hollow polymer particles with a shell of comprising crosslinked polymer of high network homogeneity.…”
Section: Hollow Particlesmentioning
confidence: 99%
“…During the FRP process, the slow initiation, fast chain propagation, and termination reactions result in the number of “dead” polymer chains increasing with time. Because of the dilute solution on the early stage, polymers of full length generate intramolecular crosslinking instead of overlapping each other, and then such chains are crosslinked together to form large molecules simultaneously absorbing more chains to produce microgels 10–22. This is undesired for ideal homogeneous polymer networks.…”
Section: Introductionmentioning
confidence: 99%